2004
DOI: 10.1097/01.pcc.0000102224.98095.0a
|View full text |Cite
|
Sign up to set email alerts
|

Predicted versus measured energy expenditure by continuous, online indirect calorimetry in ventilated, critically ill children during the early postinjury period*

Abstract: Predictive equations do not accurately predict energy expenditure in ventilated, critically ill children during the early postinjury period; if available, indirect calorimetry must be performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
59
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(65 citation statements)
references
References 46 publications
(44 reference statements)
4
59
0
2
Order By: Relevance
“…Previous studies have shown that prediction equations are not accurate to predict energy expenditure in critically ill children (34,35), because the dynamic metabolic responses to injury and illness in critically ill children render the prediction of energy needs more difficult (36). With indirect calorimetry, Metha et al (37) found that slightly more than half of patients were hypometabolic, about 25% were normometabolic, and 17% were hypermetabolic.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that prediction equations are not accurate to predict energy expenditure in critically ill children (34,35), because the dynamic metabolic responses to injury and illness in critically ill children render the prediction of energy needs more difficult (36). With indirect calorimetry, Metha et al (37) found that slightly more than half of patients were hypometabolic, about 25% were normometabolic, and 17% were hypermetabolic.…”
Section: Discussionmentioning
confidence: 99%
“…The common belief that critically ill children would be hypermetabolic has not been confirmed (19,37); on the contrary, they are more frequently hypometabolic (38). The patterns of energy expenditure, the nature of fuel utilization, and whether manipulation of these or other factors can affect patient outcome represent an important research field.…”
Section: Discussionmentioning
confidence: 99%
“…In a survey of 100 mechanically ventilated children, White et al 18 reported a mean V CO 2 and V O 2 of 5.3 and 6.3 mL/kg/min, respectively, for a cohort with a mean age of 4.5 y and a mean height of ϳ97 cm. Furthermore, in a slightly younger population with a mean age of 4.2 y, Martinez et al 19 reported a mean V CO 2 and V O 2 of 4.8 and 6.1 mL/kg/min, respectively, for a cohort of mechanically ventilated children recently admitted to the PICU. These findings suggest that the values from our study are largely in agreement with values reported elsewhere.…”
Section: Discussionmentioning
confidence: 99%